Anomalous Pulmonary Vessels – An Unusual Cause of Hemoptysis - Hoque, Mohammad Anamul; Mia, Md Mofizur Rahman; Sarkar, Nirmal Kanti; Rasha, Sheikh Md Zakirullah (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Hemoptysis is a serious medical emergency and warrants prompt and comprehensive evaluation. Anomalies of thoracic vasculature constitute an uncommon cause of hemoptysis. Pulmonary vasculature is affected by a sizeable number of anomalies. Multidetector computed tomography (MDCT) of chest is an important imaging modality for evaluating such anomalies. It plays a pithy role in the diagnosis and planning of definitive treatment by identifying the origin and course of the aberrant artery. Definitive treatment is surgical (lobectomy or segmentectomy) or endovascular approach (e.g., coiling, embolization). We report a young man with hemoptysis originating from an aberrant systemic artery arising from the descending thoracic aorta to the left lower lobe. He underwent lower lobectomy. The definite treatment led to cessation of hemoptysis. J Bangladesh Coll Phys Surg 2025; 43: 178-182